Determinants of EU greentech investments: The role of financial market conditions - Gabrielle de Haan Montes; Salome Gvetadze; Felina Lottner; Henry Milander; Xianxing Pan; Chloe Tian; Wouter Torfs (European Investment Fund (EIF), 2023)
This working paper contributes to the understanding of how Greentech ecosystems develop by considering the impact of EU countries' local financial market environment on the prevalence of Greentech investment deal activity. The empirical analysis demonstrates that the occurrence of IPOs in a country incentivises Greentech investors and entrepreneurs, and stimulates deal activity in earlier stages of the market. This suggests an important role for policy intervention at EU-level, as EU policymakers are best positioned to bridge the scale-up gap through the use of innovative financing instruments and thereby support the development of a European Greentech ecosystem.
Keywords: 330